2021
DOI: 10.1259/bjr.20210207
|View full text |Cite
|
Sign up to set email alerts
|

Lung MRI with hyperpolarised gases: current & future clinical perspectives

Abstract: The use of pulmonary MRI in a clinical setting has historically been limited. Whilst CT remains the gold-standard for structural lung imaging in many clinical indications, technical developments in ultrashort and zero echo time MRI techniques are beginning to help realise non-ionising structural imaging in certain lung disorders. In this invited review, we discuss a complementary technique – hyperpolarised (HP) gas MRI with inhaled 3He and 129Xe – a method for functional and microstructural imaging of the lung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 126 publications
(124 reference statements)
0
31
0
Order By: Relevance
“…Other imaging techniques also hold promise. For instance, polarized gas MRI can identify abnormalities in diffusion and ventilation, which may precede the development of clinically overt disease (137) .…”
Section: Lung Imagingmentioning
confidence: 99%
“…Other imaging techniques also hold promise. For instance, polarized gas MRI can identify abnormalities in diffusion and ventilation, which may precede the development of clinically overt disease (137) .…”
Section: Lung Imagingmentioning
confidence: 99%
“…Inherently low sensitivity is seen as a significant limitation of NMR spectroscopy and imaging. The most efficient way to improve NMR sensitivity is to create nuclear spin hyperpolarization, i.e ., highly nonequilibrium population of the nuclear spin states. , At the moment, several hyperpolarization techniques are available, including dissolution dynamic nuclear polarization (d-DNP), spin-exchange optical pumping (SEOP), parahydrogen-induced polarization (PHIP), and signal amplification by reversible exchange (SABRE). , d-DNP and SEOP are currently used for human biomedical applications with astounding results. , However, d-DNP and SEOP require sophisticated and expensive equipment limiting their widespread use and suffer from the long time needed for production of a hyperpolarized (HP) sample and the low duty cycles. In contrast, PHIP and SABRE are the faster and more affordable alternatives.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) of hyperpolarised xenon-129 ( 129 Xe) is an emerging research and clinical imaging modality, with demonstrated clinical impact in a range of lung pathologies such as cystic fibrosis, interstitial lung diseases, asthma and obstructive lung diseases. 1 Additionally, hyperpolarised 129 Xe MRI has been demonstrated in other organs (e . g .…”
Section: Introductionmentioning
confidence: 99%